2015
DOI: 10.1007/s12262-015-1399-0
|View full text |Cite
|
Sign up to set email alerts
|

Extraosseous Ewing Sarcoma: Diagnosis, Prognosis and Optimal Management

Abstract: Extraosseous Ewing sarcomas (EESs) are rare tumours originating from soft tissues. Their clinical picture depends mainly on the primary site of the sarcoma. Patient characteristics and outcomes seem to be different in EES compared to patients with skeletal Ewing sarcoma, with implications for patient care and prognosis. However, multimodality therapeutic strategies are recommended for all types of the Ewing tumour family. The available diagnostic tools include ultrasonographic evaluation and computed tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
1
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 51 publications
3
79
1
14
Order By: Relevance
“…Hematoxylin-eosin staining (H & E) reveals an intense blue color that defines the Ewing's sarcoma (ES) as belonging to the group of blue round cell tumors. Therefore, immunohistochemistry is an essential study for the differential diagnosis of this entity; in this case, the marker CD99 / MIC2, identified by antibody 013, was found positive, this marker is a cell membrane glycoprotein found in all ES and PNET, being reported in 98% of the cases [7]. The CD99 / MIC-2 marker has also been detected in other blue round cell tumors such as lymphoblastic lymphoma, rhabdomyosarcoma, small cell carcinoma and poorly differentiated synovial sarcoma [6], but in this case the possibility of another blue round cell tumor can be ruled out, due to the immunoreactive negativity to markers like leukocyte common antigen (CD45 / LCA), desmin and broad spectrum cytokeratin.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Hematoxylin-eosin staining (H & E) reveals an intense blue color that defines the Ewing's sarcoma (ES) as belonging to the group of blue round cell tumors. Therefore, immunohistochemistry is an essential study for the differential diagnosis of this entity; in this case, the marker CD99 / MIC2, identified by antibody 013, was found positive, this marker is a cell membrane glycoprotein found in all ES and PNET, being reported in 98% of the cases [7]. The CD99 / MIC-2 marker has also been detected in other blue round cell tumors such as lymphoblastic lymphoma, rhabdomyosarcoma, small cell carcinoma and poorly differentiated synovial sarcoma [6], but in this case the possibility of another blue round cell tumor can be ruled out, due to the immunoreactive negativity to markers like leukocyte common antigen (CD45 / LCA), desmin and broad spectrum cytokeratin.…”
Section: Discussionmentioning
confidence: 72%
“…Some authors suggest that the response of this tumor to treatment and its prognosis is directly related to the characteristics of the tumor and the age of the patient and is not determined by the tissue component, which means regardless of whether it is a bone or extraosseous Ewing's sarcoma. However, recent studies indicate that although the prognostic factors of EOES seem to be similar to osseous ES, the prognosis of this tumor in soft tissue is more favorable than in bone tissue and even more in cases of localized tumors, since it is estimated that the overall 5-year survival rate is superior in cases of localized EOES compared to localized skeletal tumors, which could explain the good evolution and response to treatment in this patient [7,8].…”
Section: Discussionmentioning
confidence: 82%
“…The median age in our studied cases was 31 years. 60 Tumour sizes >80 mm have a worse outcome than smaller tumours. The majority (64 per cent) occurred between the ages of 5 and 35 years.…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic factors for traditional ES include size, stage, age and location, 59 which are similar to that of EES. 60 Tumour sizes >80 mm have a worse outcome than smaller tumours. This is reflected in our data, which showed that 25 per cent of patients with tumours >80 mm died of the disease, compared to 21.4 per cent of patients with tumours <80 mm.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the outcome of 5-year survival rate of metastatic patients is usually poor (< 30%) compared to localised ES (65%-75%), despite the use of chemotherapy [52]. Several studies have indicated that localised extra skeletal ES has a more favourable outcome than skeletal tumours [53,54].…”
Section: Case Presentationmentioning
confidence: 99%